AN ANALYSIS ON FACTORS INFLUENCING STUDENTS’ LOW ENGLISH LEARNING ACHIEVEMENT - Chairunnisa, .; Apriliaswati, Rahayu; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research was aimed to investigate the most dominant internal and external factor influencing students’ low English learning achievement. To achieve the purpose of this study, a descriptive research was conducted at SMKN 2 Pontianak with the sample of this study was the eleventh grade students of XI TSM class in Academic Year 2015/2016 which was chosen by using purposive sampling technique. The findings of this research revealed that (1) Negative attitude was found to be the most dominant internal factor influencing students’ low English learning achievement with the percentage was 78,86% and classified as strong influence. (2) Of the two external factor, unsupportive school environment was found to be the most dominant one with the percentage was 62,38% and also classified as strong influence and followed by lack of family support with the percentage was 40,12% which was classified as weak. To conclude, negative attitude which was supported negatively by the unsupportive school environment had a strong negative influence to the teaching learning process which consequently resulted in students’ low achievement. Keywords : Internal Factors, External Factors, Low Achievement Abstrak: Penelitian ini bertujuan untuk mengetahui faktor internal dan eksternal yang paling dominan dalam mempengaruhi rendahnya hasil belajar siswa pada pelajaran bahasa Inggris. Untuk mencapai tujuan penelitian ini, sebuah penelitian deskriptif dilakukan di SMKN 2 Pontianak dengan subjek penelitian adalah siswa kelas XI TSM pada Tahun Ajaran 2015/2016 yang dipilih menggunakan teknik purposive sampling. Hasil dari penelitian ini mengungkapkan bahwa (1)Sikap negatif merupakan faktor internal yang paling dominan dalam mempengaruhi rendahnya hasil belajar siswa pada pelajaran bahasa Inggris dengan persentase sebesar 78,86% dan digolongkan sebagai pengaruh yang kuat. (2) Dari dua eksternal faktor, lingkungan sekolah yang tidak mendukung merupakan faktor eksternal yang paling dominan dengan persentase sebesar 63,38% dan juga digolongkan sebagai pengaruh kuat dan diikuti oleh kurangnya dukungan dari keluarga dengan persentase sebesar 40,12% yang digolongkan sebagai pengaruh lemah. Dapat disimpulkan bahwa sikap negatif yang didukung oleh lingkungan sekolah yang tidak mendukung memiliki pengaruh negatif yang kuat pada proses belajar mengajar yang berakibat pada rendahnya hasil belajar siswa. Kata Kunci: Faktor Internal, Faktor Eksternal, Rendahnya Hasil Belajar